Upaya Mengatasi Pengangguran di Kabupaten Kulon Progo - Sri Sumardiningsih (Universitas Negeri Yogyakarta, 2004)
This paper use 207 respondents to analyze profile and efforts to overcome unemployment problem in Kulon Progo using multi-approach of labor force. This study find that based on respondents perception, the main sources of unemployment are lack of capital, insufficient of information, low of entrepreneurship, and low of education level. In addition, it is found also that lack of work opportunity , unavailable of work opportunity matching with their skill, age factor and lack of husband or parent support. Based on those results, the author suggests some recommendation such as: widen the work opportunity in informal sector, widen the work opportunity in agriculture sector, and empowerment program of elderly people to enhance their healthiness.